Determinación de la posición de puntos elevados en la ciudad de Heredia (ING) - Moya Zamora, Jorge (Uniciencia, 2004)
The article exposes the methodology used and the results obtained in the determination of the position of inaccesible points, by means of conventional and GPS surveys. Five points were considered, located at the towers of the principal churches in the city of Heredia, Costa Rica. The coordinates obtained initially were calculated in CRTM cartographic plane, with WGS84 ellipsoid. However the official cartographic system is based on a Lambert conform conic projection, with the Clarke 1866 ellipsoid. Two variants of the coordinate transformation were done: a 4° polinomic and 7 parameter; to transform the original coordinates in CRTM plane, to the official system, in the zone called Costa Rica Norte LCRN. The difference in the application of the two transformations methods implicated certain tests and additional analysis, in order to recommend a reliable coordinate set in the official system.